Analisis Penyelesaian Sengketa Terhadap Hak Merek Atas Putusan Geprek Bensu Melawan I Am Geprek Bensu - Lompoh Egia Nuansa Pinem; Ni Luh Dwik Suryacahyani Gunadi (Jurnal Pacta Sunt Servanda, 2021)
In Indonesia, there are two forms of dispute resolution over Intellectual Property Rights. The first is through the litigation channel and the second is through the Non-Litigation route. Regarding trade disputes over trademark rights, the resolution is also through these two channels. This research specifically examines the settlement of trademark disputes between Geprek Bensu and I Am Geprek Bensu based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This research uses research methods of normative law which is carried out through the collection of primary data and secondary data as well as by the literature approach. Data analysis in this study used qualitative data analysis methods.